(3TQYI GdESdGes - (3GdLhZj, EeGe RGOg, Qcf GdESdGe (B- (3EeGe RGOg, eMeO Hf CHj HcQ, (B573 (3gs ((3MSjf Hf YKeGf Hf Ydjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj OdfG Ydi eYQaJg HGdThGgO agPg YbhO efXheI ef Sff SjO GdeQSdjf hEeGe GdeJbjf efJbOI ef cJH GdCFeI GdegJOjf ef YdeGA GdOjf eaUdI TPhQgG hYbGFdgG s
(3BNQgG (B:s
(3hef GdSfI Cf dG jPcQ ejJG ef GdeSdejf EdG HNjQ aEfg Ydjg GdSdGe CeQ HPdc hbGd dG JSHhG GdCehGJ aEfge bO CaVhG Edi eG bOehG (B, (3hbGd Ydjg GdSdGe dG JSHhG GdCehGJ aJDPhG HgG GdCMjGA hbY GdaQGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/54s
(3cTa GdXfhf (B2/1044s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs